Excellent passivation of thin silicon wafers by HF‐free hydrogen plasma etching using an industrial ICPECVD tool. Issue 1 (17th November 2014) - Tang, Muzhi; Ge, Jia; Wong, Johnson; Ling, Zhi Peng; Dippell, Torsten; Zhang, Zhenhao; Huber, Marco; Doerr, Manfred; Hohn, Oliver; Wohlfart, Peter; Aberle, Armin Gerhard; Mueller, Thomas
<x xml:space="preserve">Abstract</x> In this work, hydrogen plasma etching of surface oxides was successfully accomplished on thin (∼100 µm) planar n‐type Czochralski silicon wafers prior to intrinsic hydrogenated amorphous silicon [a‐Si:H(i)] deposition for heterojunction solar cells, using an industrial inductively coupled plasma‐enhanced chemical vapour deposition (ICPECVD) platform. The plasma etching process is intended as a dry alternative to the conventional wet‐chemical hydrofluoric acid (HF) dip for solar cell processing. After symmetrical deposition of an a‐Si:H(i) passivation layer, high effective carrier lifetimes of up to 3.7 ms are obtained, which are equivalent to effective surface recombination velocities of 1.3 cm s–1 and an implied open‐circuit voltage (Voc) of 741 mV. The passivation quality is excellent and comparable to other high quality a‐Si:H(i) passivation. High‐resolution transmission electron microscopy shows evidence of plasma‐silicon interactions and a sub‐nanometre interfacial layer. Using electron energy‐loss spectroscopy, this layer is further investigated and confirmed to be hydrogenated suboxide layers. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)